2022
DOI: 10.3390/ijms23169206
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Biomimetic Nanofibrous Scaffolds: A Promising Prospect for Bone Tissue Engineering and Regenerative Medicine

Abstract: Skeletal-related disorders such as arthritis, bone cancer, osteosarcoma, and osteoarthritis are among the most common reasons for mortality in humans at present. Nanostructured scaffolds have been discovered to be more efficient for bone regeneration than macro/micro-sized scaffolds because they sufficiently permit cell adhesion, proliferation, and chemical transformation. Nanofibrous scaffolds mimicking artificial extracellular matrices provide a natural environment for tissue regeneration owing to their larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 234 publications
1
39
0
Order By: Relevance
“…To test whether rGO exhibits cell toxicity in our system, we inoculated 3T3 cells onto the membranes and measured their proliferation using an EDU proliferation kit. The correlation between cell proliferation and cell health has previously been reported (Anjum et al, 2022). The results demonstrated that the proliferation of 3T3 cells without rGO was 40.84% ± 3.81%, whereas the proliferation ranged from 36.24% ± 7.25% to 44.88% ± 10.28% for the membranes with rGO (Figure 4C).…”
Section: Biocompatibility Of the Rgo/plcl Membranes In Vitrosupporting
confidence: 79%
“…To test whether rGO exhibits cell toxicity in our system, we inoculated 3T3 cells onto the membranes and measured their proliferation using an EDU proliferation kit. The correlation between cell proliferation and cell health has previously been reported (Anjum et al, 2022). The results demonstrated that the proliferation of 3T3 cells without rGO was 40.84% ± 3.81%, whereas the proliferation ranged from 36.24% ± 7.25% to 44.88% ± 10.28% for the membranes with rGO (Figure 4C).…”
Section: Biocompatibility Of the Rgo/plcl Membranes In Vitrosupporting
confidence: 79%
“…Among these, nanofibers are being widely used for effective treatment because of their multifunctional and distinctive properties, including a large surface area:volume (SA:V) ratio, satisfactory stiffness and resistance to traction, favorable biodegradability, high elasticity and permeability, and a sufficient oxygen supply that maintain the moisture content of the skin and improve the bioavailability of the drug. The nanofibers mimic the extracellular matrix (ECM) to promote skin regeneration capacity and enable a controlled-release pattern compared with other conventional therapies. , Electrospinning is the most widely used nanofiber fabrication technology as this is a very simple, user-friendly, and cost-effective technique that yields ultrafine fibers . Prepared nanofiber mats loaded with dual drugs in polymeric nanofibers have been used to facilitate specific drug-targeted delivery and to enable optimized active component protection as well as favorable therapeutic activity .…”
Section: Introductionmentioning
confidence: 99%
“…Bone grafts and bone replacements are currently the routine treatment options applied for 2.2 million surgeries per year [ 5 , 6 ]. However, as an invasive surgery, the risk of immune rejection and cross infection caused by bone graft is often unavoidable after surgery [ 7 , 8 ]. Therefore, bone grafting and bone replacement surgery are limited in some situations.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike permanent bone implants, scaffolds are implanted to provide effective temporary support for cell adhesion. Multiple reports have demonstrated nanostructured scaffolds are more efficient than macrosized scaffolds in promoting bone regeneration [ 7 ]. Because nanoscaffolds have large surface areas and high porosity, they artificially mimic the extracellular matrix to a certain extent, providing an excellent natural environment for tissue regeneration processes, including cell adhesion, proliferation and differentiation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%